Adiponectin levels in a large pooled plaque psoriasis study population. (3rd July 2020) - Gerdes, S.; Pinter, A.; Biermann, M.; Papavassilis, C.; Reinhardt, M.
Abstract: Background: Adiponectin is an adipocyte-secreted protein potentially relevant in the context of cardiometabolic comorbidity of psoriasis patients. Objective: This post-hoc analysis aimed to assess the impact of obesity, metabolic syndrome, psoriasis severity and treatment with secukinumab/etanercept on adiponectin. Methods: Three phase III trials in moderate to severe plaque psoriasis were included. Correlations of Psoriasis Area and Severity Index (PASI), body mass index (BMI), and associated comorbidity with adiponectin levels as well as the impact of secukinumab, etanercept, and placebo were analyzed. Results: Data of 3010 patients were included of whom 71.2% had a BMI >25. Adiponectin levels were significantly higher in patients with lower BMI ( r  = −0.23; p  < .0001) and in patients without metabolic syndrome compared to patients with higher BMI and with metabolic syndrome. PASI score was negatively associated with adiponectin levels ( r  = −0.065; p  = .0004). However, the correlation was extremely weak and thus clinically irrelevant. During treatment with secukinumab or etanercept over 52 weeks adiponectin levels remained stable. Conclusion: Metabolic syndrome and BMI are key determinants of adiponectin levels in psoriasis patients. Psoriasis severity and anti-psoriatic treatment had no relevant impact on adiponectin levels.